Chasing the rainbow: lesbian, gay, bisexual, transgender and queer youth and pride semiotics - Wolowic, Jennifer M. (Cult Health Sex, 2016)
While the pride rainbow has been part of political and social intervention for decades, few have researched how lesbian, gay, bisexual, transgender and queer young people perceive and use the symbol. How do lesbian, gay, bisexual, transgender and queer youth who experience greater feelings of isolation and discrimination than heterosexual youth recognise and deploy the symbol? As part of a larger study on supportive lesbian, gay, bisexual, transgender and queer youth environments, we conducted 66 go-along interviews with lesbian, gay, bisexual, transgender and queer youth people from Massachusetts, Minnesota and British Columbia. During interviews, young people identified visible symbols of support, including recognition and the use of the pride rainbow. A semiotic analysis reveals that young people use the rainbow to construct meanings related to affiliation and positive feelings about themselves, different communities and their futures. Constructed and shared meanings help make the symbol a useful tool for navigating social and physical surroundings. As part of this process, however, young people also recognize that there are limits to the symbolism; it is useful for navigation but its display does not always guarantee supportive places and people. Thus, the pride rainbow connotes safety and support, but using it as a tool for navigation is a learned activity that requires caution.